IDENTIFIKASI SWOT DAN PENENTUAN STRATEGI PENGEMBANGAN KOPERASI MAHASISWA - Octaviani, Anis Nur; Yandri, Pitri (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2023)
A cooperative is an organizational entity that prioritizes the principle of kinship in its operations. As an organization, cooperatives must establish a strategy to develop their organization. In determining the process, several things must be considered by the leadership of the organization for the sustainability of the organization. Using SWOT analysis, organizational leaders can find out how the internal conditions and external conditions of the organization. This research was conducted to analyze the needs of the external and internal environment of the organization, analyze the current strategies applied, and develop the best strategies that leaders can use in developing their operations. We conducted research at the Student Cooperative of Institut Teknologi & Bisnis Ahmad Dahlan, Jakarta. Data collection using surveys by observation instruments, interviews, and questionnaires. The analytical method used is quantitative SWOT. The results showed that there are strengths and weaknesses in the internal environment as well as opportunities and threats from the external environment. We later learned that the strength score was above the weakness score, and the chance score was above the threat score. In our research, we found that the internal problems of student cooperatives lie in the lack of participation of members in cooperative activities and the lack of communication between members, which causes different perceptions between them. From the external side, the problems include marketing channels and a lack of capital in marketing. Then, the quantitative SWOT analysis results show that the cooperative's position is in the first quadrant, which means that cooperative leaders pursue an aggressive growth strategy